Effects of adding bulking agents on biostabilization and drying of municipal solid waste. (April 2017) - Yuan, Jing; Zhang, Difang; Li, Yun; Chadwick, David; Li, Guoxue; Li, Yu; Du, Longlong
Highlights: MSW bio-drying with bulking agent increased waste temperature and water-removal. MSW bio-drying with cornstalks achieved the highest bio-drying index. Lipids and cellulose were the main volatile solids losses during MSW bio-drying. Latent heat of evaporation was the main heat consumption source during bio-drying. Abstract: The influence of adding a bulking agent on the bio-stabilization and drying of municipal solid waste (MSW) was investigated. Three treatments were considered: the addition of either cornstalks or wood peat to MSW as a bulking agent before bio-drying and a control treatment that contained no bulking agent. Addition of bulking agents to MSW produced less leachate, higher moisture-removal rates, and consumed less volatile solids. Bulking with cornstalks achieved the highest water-removal rate (0.58–0.65 kg kg −1 ). The extent of organic degradation was related to temperature integration during bio-drying. Lipids and cellulose were the main components of organic losses in all treatments and adding a bulking agent changed the sequence and extent of degradation of biochemical components. The bio-drying index values were 1.75, 3.18, and 2.64 for MSW alone, MSW with cornstalks, and MSW with wood peat, respectively. Evaporation heat was the main component of heat consumption, accounting for 58.1–60.7% of the total energy consumption.